2019
DOI: 10.3389/fpsyt.2019.00780
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Late Pregnancy Disrupt Attentional Processing of Negative–Positive Emotion: An Eye-Movement Study

Abstract: This study investigated biases for negative–positive information in component processes of visual attention (initial shift vs. maintenance of gaze) among women in late pregnancy with or without depressive symptoms. Eye movements were recorded while participants viewed a series of picture pairs depicting negative, positive, and neutral scenes. Initial orienting (latency and percentage of first fixation) and gaze duration were computed. Compared with neutral pictures, the group with major depressive symptoms (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…This finding was unexpected as previous studies showed that depressed mothers were less likely to identify happy infant faces ( 76 ) and rated negative infant faces more negatively ( 39 ). Different attentional processing of positive and negative infant emotions associated with depression symptoms was evident even during pregnancy ( 77 , 78 ). A similar effect of depression was demonstrated in fathers, as well.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was unexpected as previous studies showed that depressed mothers were less likely to identify happy infant faces ( 76 ) and rated negative infant faces more negatively ( 39 ). Different attentional processing of positive and negative infant emotions associated with depression symptoms was evident even during pregnancy ( 77 , 78 ). A similar effect of depression was demonstrated in fathers, as well.…”
Section: Discussionmentioning
confidence: 99%
“…The scale comprises 10 items, each item is scored according to the severity of symptoms (0–3 points), with total possible scores ranging from 0 to 30 points. The higher the score, the more severe the symptoms of depression [ 35 ]. This scale has good reliability and validity in mainland China [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, as early components of ERP in emotion processing, N1 in both the visual modality [31,32] and the auditory modality [33] reflect early attention to emotional stimuli. Larger N1 amplitudes have been observed in response to emotional pictures [26,34] and emotional audio recordings [33,35] as compared to neutral stimuli. In addition, the late positive potential (LPP) in the visual modality and the late negative component (LNC) in the auditory modality are late components of ERP in emotion processing that are thought to be an indicator of the evaluation of emotional information [36,37].…”
Section: Introductionmentioning
confidence: 94%
“…Although several studies have shown that the perception of social stimuli is altered in individuals with ASD or autistic traits [16,17,23,25,26] these studies only used neutral social stimuli. Mental processing in individuals with ASD [27] or autistic traits [28,29] has been found to differ depending on the emotional valence of the stimulus, in that such individuals exhibit worse recognition of stimuli with negative rather than positive emotional valence.…”
Section: Introductionmentioning
confidence: 99%